Development of a real-time spalling measurement system for ball-type constant velocity joints. (December 2021) - Song, Jun; Kim, Dong Hyuk; Kim, Seong Han
Highlights: A novel system to measure the wear depth and spalling in ball type CV joints. The kinematics of the CV joints was perfectly implemented in the system. The system measures the wear depth of a CV joint and detects spalling phenomena. The wear depth results were verified by the results from the profilometer. Abstract: This study proposes a measurement system to detect spalling phenomena of ball-type constant velocity joints (CVJ). The spalling phenomena that usually occur in the inner race of a CVJ are a significant factor to the CVJ's life, but it is very difficult to measure the spalling because the inner race is mechanically enclosed by an outer race and a cage. The developed system can not only detect the spalling but also measure the depth of adhesive wear in real time by implementing kinematics and applying force to an individual ball-type CVJ. The kinematics of a CVJ was analyzed to ensure that the measurement system operates the same as the actual CVJ. Especially, reciprocal yaw motions in the ball-type CVJ were perfectly implemented to the system. The system consists of three subsystems. The first system applies normal force to the contact points. Ball screws, spur gears attached to the motor amplify the force. The second system creates the reciprocal yaw motion with the same profiles as an actual CVJ. The third system is the measurement part, consisting of an incremental rotary encoder and a load cell. The resolution of wear depth is amplified and achieves up to 0.18°/μm. For validation, a ball-type CVJ was chosen and its spalling depth was measured. The results were verified by comparing the system measurement data with the profilometer measurement data.